Use of phase diagrams to guide ceramic production from wastes - Segadaes, A M (Advances in applied ceramics, 2006)
While natural raw materials are becoming scarce and in some cases approach exhaustion, continuous industrial activity generates increasing quantities of wastes and subproducts, whose disposal is subject to ever stricter environmental legislation. Some wastes are similar in composition to the natural raw materials used in the fabrication of ceramics and often contain materials that are also beneficial in the fabrication process. Thus, upgrading industrial wastes to alternative raw materials is of interest both technically and economically. The present paper sets out the reasoning behind the use of phase diagrams to guide ceramic production, namely the assumptions necessary in making educated choices of compositions and processing parameters. It goes on to show how adequate dexterity with the diagrams' basic rules and dictates, coupled with sound knowledge of ceramic science and processing, can save time and resources, and eventually lead to successful upgrading of the waste material and amelioration of its negative impact on the environment.